Pemanfaatan video dalam pembelajaran pancasila dan kewarganegaraan untuk meningkatkan kemampuan berpikir kritis siswa terhadap kebijakan publik - Jossapat Hendra Prijanto (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
The learning objectives of Pancasila and Citizenship should be used as a way in increasing nationalism, and that form of nationalism should be embodied in concerning of public policy. Every Indonesian citizen participates in increasing society’s life which is fair, peaceful, and prosperous in Pancasila and Citizenship subject, the researcher asks the students to make LOC (Letter of Concern) video which should be uploaded on YouTube. The authorities are also expected to be able in taking wise public decisions. This research method is using literature study that is finding theory reference which is relevant with a case or problems that is found. This is the role of Pancasila and Citizenship learning as a tool in character building, especially for increasing the concern of Indonesian citizens in society, nation, and state’s life.Keywords: LOC (Letter of Concern) Video, Pancasila and Citizenship Learning, Critical Thinking, Public Policy http://dx.doi.org/10.17977/um022v2i12017p006